KEJADIAN KEGUGURAN DITINJAU DARI UMUR IBU DI BPS ITA ARIANI WONOAYU SIDOARJO - Ika Mardiyanti (Jurnal Ilmiah Kesehatan, 2015)
The incidence of Abortion in terms of the maternal age in The Private Midwife Clinic of Ita Ariani Wonoayu Sidoarjo. Maternal Mortality Rate in Indonesia is still high about 206 over 100.000 life births. Abortion is one of the cause of maternal mortality rate. And pregnant mother who had age ( < 20 and > 35 tahun years old) is more get abortion. The purpose of this research is to analyze the correlation between maternal age with the occurance of abortion in The Private Midwife Clinic of Ita Ariani Wonoayu Sidoarjo. Design of this research is observational analytic using cross sectional method. Population of this research is 15 pregnant mothers with pregnancy age less than 20 weeks. Sample of this research as many as 14 people with simple random sampling technique. The independent variable is maternal age and the dependent variable is occurance of abortion. The data is collected from medical record and analyzed by using Chi – Square test. Result of this research show that most of respondents are pregnant mother who had low risk age (20 – 35 years old) as many as 8 people (57,1%) and pregnant mother who got abortion as many as 5 people (35,7%). Based from Chi–Square test show that P = 0,001 < α = 0,05 and it is mean that there is correlation between mother age with the occurance of abortion. The conclusion of this research is mother age is one of the cause of abortion. Pregnant mother who had younger age (< 20 years old) and older age (> 35 years old), the probability of abortion is higher so pregnant mother must do ANC regularly.